Strategi Kolaborasi Pemerintah dan Masyarakat dalam Penanggulangan Fakir Miskin di Wilayah Perkotaan Kabupaten Tolitoli - Muhammad Iqbal; Nursifa; Zaskia (Tolis Ilmiah : Jurnal Penelitian, 2026)
This study analyzes the collaborative strategy between the government and the community to address poverty in the urban areas of Tolitoli Regency. The study was conducted in Baolan District, Tolitoli Regency. The method used was a qualitative, descriptive-explanatory approach with purposive selection of informants, observation, in-depth interviews, and FGDs; data analysis followed the approach of Miles, Huberman, and Saldana, combined with Geoff Mulgan's strategic framework (purpose, environment, direction, action, learning). The results showed that: the objectives of government and community collaboration were recognized normatively but had not been internalized into operational practices so that program priorities and community participation were inconsistent; complex environmental conditions and poor quality data on prospective recipients increased the risk of inclusion and exclusion; formal strategic direction was available but day-to-day implementation depended on intermediate actors with varying capacities, resulting in inconsistencies; and learning and evaluation mechanisms were not yet integrated so that field feedback rarely changed policy.